The Effectiveness of the Project-Based Learning (PjBL) Model on Students’ Creativity - Rina Martiana; Lalu Muh Rudi Susanto; Khaerul Anam; Heri Rismawan (Indonesian Journal of Educational Innovation, 2025)
The use of teacher-centred learning in schools has become a common issue in education. This study aims to analyze the effectiveness of the Project-Based Learning (PjBL) model on students' creativity. The objective of this study is to examine and analyze the effectiveness of the ProjectBased Learning (PjBL) model in enhancing students' creativity. The research method employed a quantitative descriptive approach with a one-group pretest-posttest design, involving 18 students from class XI at MA Pondok Pesantren Darul Muhsinin as the sample. Data was collected through tests. The analysis results showed that the implementation of PjBL in class XI increased student scores, improving learning outcomes from a pretest score of 38.6 to a posttest score of 67.7. There was a significant difference between the pretest and posttest scores, indicating that Project-Based Learning is an effective method for enhancing students' creativity in learning.